Bulk Spin Torque‐Driven Perpendicular Magnetization Switching in L10 FePt Single Layer. Issue 31 (28th June 2020) - Tang, Meng; Shen, Ka; Xu, Shijie; Yang, Huanglin; Hu, Shuai; Lü, Weiming; Li, Changjian; Li, Mengsha; Yuan, Zhe; Pennycook, Stephen J.; Xia, Ke; Manchon, Aurelien; et al.
Abstract: Due to its inherent superior perpendicular magnetocrystalline anisotropy, the FePt in L 10 phase enables magnetic storage and memory devices with ultrahigh capacity. However, reversing the FePt magnetic state, and therefore encoding information, has proven to be extremely difficult. Here, it is demonstrated that an electric current can exert a large spin torque on an L 10 FePt magnet, ultimately leading to reversible magnetization switching. The spin torque monotonically increases with increasing FePt thickness, exhibiting a bulk characteristic. Meanwhile, the spin torque effective fields and switching efficiency increase as the FePt approaches higher chemical ordering with stronger spin–orbit coupling. The symmetry breaking that generates spin torque within L 10 FePt is shown to arise from an inherent structural gradient along the film normal direction. By artificially reversing the structural gradient, an opposite spin torque effect in L 10 FePt is demonstrated. At last, the role of the disorder gradient in generating a substantial torque in a single ferromagnet is supported by theoretical calculations. These results will push forward the frontier of material systems for generating spin torques and will have a transformative impact on magnetic storage and spin memory devices with simple architecture, ultrahigh density, and readily application. Abstract : Bulk spin torque‐driven perpendicular magnetization switching in an L 10 FePt single‐layer arises from an inherent structural gradient and exhibits great potential for removing the fundamental obstacles faced by conventional spin–orbit torque devices, such as thermal stability issues and complexity issues regarding three‐terminal operation.